Mutation of a common amino acid in NKX2.5 results in dilated cardiomyopathy in two large families. Issue 1 (December 2016) - Hanley, Alan; Walsh, Katie; Joyce, Caroline; McLellan, Michael; Clauss, Sebastian; Hagen, Amaya; Shea, Marisa; Tucker, Nathan; Lin, Honghuang; Fahy, Gerard; Ellinor, Patrick
Abstract Background The genetic basis for dilated cardiomyopathy (DCM) can be difficult to determine, particularly in familial cases with complex phenotypes. Next generation sequencing may be useful in the management of such cases. Methods We report two large families with pleiotropic inherited cardiomyopathy. In addition to DCM, the phenotypes included atrial and ventricular septal defects, cardiac arrhythmia and sudden death. Probands underwent whole exome sequencing to identify potentially causative variants. Results Each whole exome sequence yielded over 18, 000 variants. We identified distinct mutations affecting a common amino acid inNKX2.5 . Segregation analysis of the families support the pathogenic role of these variants. Conclusion Our study emphasizes the utility of next generation sequencing in identifying causative mutations in complex inherited cardiac disease. We also report a novel pathogenic NKX2.5 mutation.